2013
DOI: 10.1590/s0365-05962013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of weathering nodules of the ear in patients treated at the state civil servant's hospital of São Paulo, Brazil*

Abstract: BACKGROUNDWeathering nodules of the ear are pale yellow, asymptomatic lesions which predominate on the helices of the ears. Although their pathogenesis remains unknown, there is an association with chronic exposure to ultraviolet radiation, age and thermal injuries. Few studies have been conducted to date, and these involved a very small number of patients. OBJECTIVEStudy the prevalence of weathering nodules of the ear in patients treated in the Dermatology Service of the State Civil Servant's Hospital of São … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…Weathering nodules were also found to be more common within the tropical population studied (38.8%, 155/400) when compared to a nontropical population (4%, 4/100). [ 1 5 ] These data support the hypothesis that sun exposure has a significant role in the pathogenesis of these lesions. In addition, weathering nodules were previously thought to be found exclusively in white- or light-skinned populations; indeed, they had previously been described as “a condition found on Caucasian men who have a history of significant cumulative sun exposure.”[ 7 ] Although this claim was substantiated by earlier individual case reports, an epidemiologic study recently described five patients (17%, 5/29) with Fitzpatrick skin phototype V who had weathering nodules.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Weathering nodules were also found to be more common within the tropical population studied (38.8%, 155/400) when compared to a nontropical population (4%, 4/100). [ 1 5 ] These data support the hypothesis that sun exposure has a significant role in the pathogenesis of these lesions. In addition, weathering nodules were previously thought to be found exclusively in white- or light-skinned populations; indeed, they had previously been described as “a condition found on Caucasian men who have a history of significant cumulative sun exposure.”[ 7 ] Although this claim was substantiated by earlier individual case reports, an epidemiologic study recently described five patients (17%, 5/29) with Fitzpatrick skin phototype V who had weathering nodules.…”
Section: Discussionsupporting
confidence: 75%
“…However, a more recent epidemiologic study of 400 patients performed on a tropical population (Brazil) found an increased incidence of weathering nodules in women. [ 5 ] They observed weathering nodules in 81 of 230 women as compared to 74 of 170 men. [ 5 ] It has been proposed that women's ears are normally protected from the sun by their long hair, protecting them from sun-induced ear damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations